Desempenho de cordeiros e ovelhas até o desmame, de raças puras e cruzadas - (:unkn) unknown (Universidade Federal do Pampa, 2012)
With the intensification of production systems for meat, it is possible obtain satisfactory performance of the lambs kept at the foot of the mother from birth to weaning. This study evaluated the performance through the average daily gain (ADG) of lambs kept at the foot of the mother from birth to weaning of purebred and cross, body condition score (BCS) and weights of lambs to weaning. The study was conducted between the months of June to December 2011, the municipality of Dom Pedrito, with four genotypes, as follows: Texel, Corriedale, Dorper/Texel and White Dorper/Corriedale. The animals remained on continuous grazing in an area of 130 hectares of field native improved during the experimental time. The performance evaluations of all sheep/lamb were collected at 45,75 and 105 days old, and the dates the ratings were calculated by averaging the first and last birth .In the time of weaning, obtaining the weighing was performed the settlement of weight for the 105 days of age. The results showed that the ADG and weight adjusted to 105 days were different between the pure breeds, and there was no difference between the others. To assess birth weight crosses the White Dorper x Corriedale differed only with the pure. The comparison between males and females differed only for the weight adjusted to 105 days. In the evaluation of weaning weight difference of the sheep occurred only with pure Texel females when compared with the other. For the BCS results showed that for the purebred Texel females differed only with Corriedale and White Dorper/Corriedale. Concluding that the performances of the whole sheep / lamb for both genotypes were relevant and satisfactory.
Keywords: Campo nativo melhorado; Ganho médio diário; Genótipo; Ovinos; Zootecnia; Average daily gain; Improved native field; Genotype; Sheep; Zootechny; CNPQ::CIENCIAS AGRARIAS